Strengthening Local Residents’ Capacity for Community-Based Environmental Monitoring in the Mining Area of Mimika, Central Papua - Obed Patiung; Frederik Irsan Delu; Abd. Rahim; Nilam Sry Putri; Mapuay Menasye Theo Afasedanya; Oktavianty Batto (Sakura Digital Nusantara, 2026)
Mimika Regency, Central Papua, is a socially and ecologically significant area due to its strong connection with mineral mining activities, which require local communities to have adequate environmental literacy and basic monitoring capacity. This community service program aimed to strengthen local residents’ understanding of mining-related environmental risks and improve their ability to conduct simple community-based environmental monitoring. The program was conducted in Atuka Village, Mimika Tengah District, Mimika Regency, Central Papua, involving 10 participants consisting of local residents, community leaders, youth representatives, and local community groups. A participatory-educational approach was applied through four stages: needs assessment, environmental literacy education, simple environmental monitoring training, and evaluation followed by action planning. The training materials covered mining-related environmental impacts, reclamation and post-mining concepts, simple water quality observation, dust and noise identification, and community-based environmental reporting. The results showed that participants’ understanding increased from an average pre-test score of 49.4 to an average post-test score of 79.8, indicating an improvement of 30.4 points. The program also produced a simple environmental monitoring sheet and an initial plan to establish a community-based environmental monitoring group. These findings indicate that practical environmental literacy training can serve as an initial empowerment model for promoting community participation, transparent communication, and sustainable environmental governance in mining-related areas.